Public funding of innovation projects: Is it zime for a more flexible approach? - Christian Rammer; Ronald Klingebiel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
Increasing investment in innovation has been a major goal of research and innovation policy in Europe over the past decade. Yet to secure competitive advantage and achieve growth, R&D investment has to be translated into successful innovations, and this is first and foremost the task of firms. Turning R&D into successful innovation is a tricky business, however. Consequently, managerial economics has proposed a variety of approaches for getting the most out of R&D investments. A recent study funded under the SEEK research programme examined the use of flexible resource allocation as a management tool for achieving successful product innovation. – – Jahr für Jahr fördern die Europäische Union und ihre Mitgliedsstaaten mit Millionen von Euro Forschung und Entwicklung (FuE) sowie Innovationsprojekte in Unternehmen. Ziel ist es, die Wettbewerbsfähigkeit Europas zu stärken. Der Erfolg staatlicher Förderprogramme und damit der Ertrag jedes eingesetzten Euros ließe sich allerdings deutlich steigern, wenn das derzeit eher starre Modell der staatlichen Förderung stärker flexibilisiert würde. Zu diesem Ergebnis kommt eine Studie, die das Zentrum für Europäische Wirtschaftsforschung (ZEW) gemeinsam mit der Warwick Business School im Rahmen des SEEK-Forschungsprogramms durchgeführt hat.
Keywords: 330